Learner autonomy in higher education: towards a validation of the PRO-SDLS scale to Portuguese engineering students - Duarte, M. (2013)
Learner autonomy and self-direction in learning in higher education has become increasingly important as the focus changes from the teacher to the learner. Lifelong learning and the ability to continuously learn are only possible if students have more control of their own learning. This study is a first step towards an adaptation and validation of a Portuguese version of the Personal Responsibility Orientation to Self-Direction in Learning Scale (PRO-SDLS) to undergraduate engineering students. Using factor and reliability analysis, 12 items of the translated scale showed strong validity and reliability. The findings indicate that the PRO-SDLS can be used with engineering undergraduate students. More data collection and confirmatory analysis is suggested.